Pengaruh Motivasi Kerja, Pengembangan Karyawan, dan Kompensasi terhadap Turnover Karyawan pada Perusahaan PT LKMAK - Bela Annisa Rizqika Mufti; Albert Surya Wanasida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of work motivation, employee development, and compensation on employee turnover at PT LKMAK. A quantitative approach was employed, utilizing Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The findings reveal that work motivation and employee development have a negative effect on turnover, indicating that increased motivation and the availability of relevant development programs can reduce employees’ intention to leave the organization. In contrast, compensation shows a positive effect on turnover, suggesting that increasing financial rewards without sufficient support from intrinsic and non-financial factors may lead to higher turnover intention. These results underscore the importance of strategically managing motivation and employee development, as well as designing a fair compensation system to effectively minimize employee turnover.